Assembly of biosolar cells by using N719-bacteriorhodopsin complex - Nesari, Mina; Molaeirad, Ahmad (Archives of Advances in Biosciences, 2016)
Today, using new and renewable energy sources to replace fossil fuels is greatly expanded. The solar cells are devices that convert solar energy to electrical energy. Solar cells based on organic materials, especially proteins, are one of these solar cells. For example, bacteriorhodopsin (bR) which is one of the membrane proteins in halobacterium salinarum could be used in solar cells and participate in the liberation and transfer of the electrons. In this study, the effort has been to add a chemical dye (N719) to protein and develop a new hybrid bR/Dye complex to increase efficiency of solar cells based on protein. The formed hybrid complex was tested by using of FTIR and other spectroscopy. Current and voltage of bacteriorhodopsin-based photocell was increased in new complex-based photocell. The results of AFM, FTIR and UV-Visible spectroscopy showed a smooth deposition of bR-Dye N719; stable complex of bR-Dye N719 was also formed.